Views and experiences of using advanced technologies in higher education of healthcare professionals: A systematic mixed-method review - Atout, Maha; Nalubega, Sylivia (Frontiers in Education, 2023)
While it is highly recommended to adopt technology in higher education of healthcare professionals, user experiences have not been widely studied. This review investigates the experience of using technology within healthcare higher education, in an attempt to gather useful insights into how use of such technologies can be improved. Both quantitative and qualitative data was used for this mixed-method review.The findings revealed many benefits associated with technology use, which included; improved clinical competency, improved overall quality of education and improved peer networking. However, there were numerous factors which hindered the widespread adoption of advanced technology. These factors included; the high costs involved, a lack of adequate equipment and a lack of understanding in such technology. While the use of advanced technology for the training of healthcare professionals is generally embraced, it is not without problems. It is necessary for institutions to offer relevant and accessible support to both students and teachers, in order to improve the use of such technology in teaching and learning practice.